Unleashing the Power of Digitization: National Mission for Manuscript’s Analysis and Special Efforts in Enhancing Manuscript Usability and Preserving Cultural Heritage in Uttar Pradesh - Jaiswal, Priyanka; Chaurasia, Abhay; Singh, Ajay Pratap (International Journal of Knowledge Content Development & Technology, 2024)
The present study focuses on the activities and efforts of the National Mission for Manuscripts (NMM) in the Uttar Pradesh region, which is known for its vast area, population, and rich cultural heritage. The aim is to examine the digitization work carried out by the NMM in this area, as digitization plays a crucial role in preserving our country’s rich ancient heritage. The importance of safeguarding cultural heritage is universally acknowledged, and digitization serves as a vital tool in this endeavour. Through digitization, we can protect and preserve our heritage for future generations. The government has implemented several commendable initiatives for manuscript digitization, and the NMM stands as a prominent organization dedicated to the conservation of cultural heritage. The NMM possesses a diverse range of cultural heritage resources, including photographic slides, photographs, digital images, photo-negatives, motion pictures, audio spools, microfiche, LP records, endangered manuscripts, audio and videotapes, digital images, microfilms, digital audio and video files, and more. The mission has undertaken extensive digitization efforts to conserve and provide access to a significant portion of its collection. This study is unique as it explores the digital conservation and digitization practices of a premier institute working in the field of art and cultural heritage in Uttar Pradesh. With its extensive network of institutions, the mission aims to cover all manuscripts, digitize them, and consolidate them on a common platform for easy access and utilization.